Բռնի մահմեդականացված հայության բեկորները Ղարաբաղում - Հովհաննիսյան, Լեռնիկ (ԱրՊՀ հրատ․)
This article refers to the Islamized Armenians on the territory of Artsakh. The Turkic-speaking conquerors settled in Artsakh in Armenian environ-ment changed not only the ethnic composition of population, but also distorted the historical-cultural values and national differences that even-tually led to the loss of national characteristics and assimilation of some part of the Armenians of Artsak. В настоящей статье говорится об исламизированных армянах на территории Арцаха. Тюркоязычные завоеватели обосновавшись в Арцахе в армянской среде изменили не только этнический состав населения, но и исказили историко-культурные ценности и национальные отличия, что в конечном итоге привело к потере национальных особенностей и ассимиляции некоторой части армян Арцаха.
Keywords: Հայագիտություն; Արցախ